(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The conscience: a reflection from antiquity to the modern age The article analyzes the term „conscience” from an etymological, theological and philosophical point of view. It specifically highlights the content and meaning of „conscience” in antiquity (Greek and Roman cultures) and in the Holy Scriptures. From the perspective of Protestant theology, Dr. Martin Luther - as an important representative - rephrased this term by giving it a new meaning. While Pope Pius XII presents from a Catholic perspective the practical aspect of „conscience”, German philosophers of Jewish origin such as E. Kant and F. Nietzsche analyze this concept in a modern manner, remarkably influencing the theological thinking of the century XX.